Cyber-Publics and ahe Corporate Control of Online Communication - Dahlberg, Lincoln (Javnost-The Public, 2004)
The Internet has enabled many individuals and groups to articulate and contest positions on a myriad of local, national, and international issues, thereby extending the public sphere(s) of critical communication at the heart of strong democracy. However, a number of commentators argue that this critical communication is likely to become ever more restricted given the increasing corporate ownership and control of cyberspace. In this paper, I undertake a general investigation of this corporate takeover and the limits it places on the possibility of the Internet extending the public sphere. Focusing primarily upon the United States, I find that the increasing ownership of the network’s content, code, and bandwidth by a few huge vertically and horizontally integrated media corporations is providing the basis for the control of online communication. Content discrimination is already being undertaken by some broadband network providers. These trends suggest that the Internet is being developed toward an arena where critical voices and practices will be increasingly marginalised. Given this situation, significant steps will be needed to secure and extend online critical communication. I conclude by suggesting a number of such steps, focusing upon legislative measures that should be urgently considered by Internet researchers and policy makers.